PENGARUH HARGA DAN PRASARANA TERHADAP KEPUASAN MAHASISWA S1 AKUNTANSI UNIVERSITAS PAMULANG - Sri Nitta (JURNAL AKUNTANSI BARELANG, 2018)
This research aims to obtain evidences empirically about the influence of Price and Infrastucture to Customer Satisfaction either partially or simultaneously. The data used in this research is primary data by using questionnaires. The sampling technique is using purposive sampling. The subject of this research is students in Accounting S1 Economic Faculty who have been studying by taking sample of 100 respondents. Respondents' answers on the questionnaires were analyzed by using multiple linear regression analysis using SPSS 22.00 for then to be concluded. The results showed that price and infrastructure simultaneously influence customer satisfaction. Partial test concluded that price and infrastructure have positive and significant effects on customer satisfaction.